PULSUS FREQUENCY OF BALI CATTLE IN THE FIRST TRIMESTER OF GESTATION AT BALI CATTLE BREEDING CENTER SOBANGAN VILLAGE, MENGWI BADUNG - Jinorati, Kristiana Yoaltiva; Suartha, I Nyoman; Gunatha, I Ketut (Buletin Veteriner Udayana; Vol. 8 No. 2 Agustus 2016, 2016)
This study aim was to determine pulsus frequency of bali cattle in first trimester of gestation. The first trimester of gestation is a vulnerable periods of fetal death . One effort to reduce the failure rate of production due to reproductive disorders during the first trimester of gestation by conducting praesen status. Things that include of praesen status are pulsus frequency. The specific study of normal standard values of bali cattle praesen status during gestation, especially frequency pulsus is not yet available.This research used fifteen bali catlle with first trimester of gestation with clinically health. Pulsus frequency determined by palpating the artery at coccygeal area. The result showed that pulsus frequency 76.66±7.88 times/minute. The result can be used as an indicator to determine bali cattle gestation of health.
Keywords: sapi bali, frekuensi pulsus, kebuntingan trimester pertama, bali cattle, pulsus frequency, first trimester of gestation